Scientific Reasoning, Critical Thinking, and Academic Performance in Science of Selected Filipino Senior High School Students - Mae F. Farillon, Leah (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
This correlational study on quantitative in nature was conducted to determine the relationship of scientific reasoning skills, critical thinking skills, and performance in Science of senior high school (SHS) students at Tapaz National High School, Capiz, Philippines. The variables in this study are the six different strands in SHS, namely, Science, Technology, Engineering, and Mathematics (STEM); General Academic Strand (GAS); Accountancy, Business, and Management (ABM); Home Economics (HE); Information and Communications Technology (ICT); and Shielded Metal Arc Welding (SMAW). The study used three instruments to quantify its goal with the statistical tools used to analyse data, i.e. the mean, standard deviation, and Pearson's r correlation coefficient. All inferential tests were set at 0.05 alpha level. The findings of the study revealed that the level of scientific reasoning skills of SHS students when taken as a whole was